Hierarchology and hierarchography - Petrič, Karl (knjige, 2025)
Hierarchology with hierarchography is an interdisciplinary science that studies hierarchical associative systems and their connections within individuals, society, and nature. The theoretical concept of hierarchology is intended to be sufficiently universal to provide a rigorous and efficient framework for scientific research across multiple disciplines and to facilitate the synthesis of diverse forms of knowledge, including with the support of artificial intelligence systems.
Keywords: družba; družina; duhovnost; hierarhični asociativni sistemi; hierarhologija; interdisciplinarnost; miselni proces; mišljenje; narava; psihologija; Znanost